New Discovery of Late Pleistocene Vertebrate Fossils from the Thimi Formation, Bhaktapur, Nepal - Paudayal, Khum N. (Journal of Institute of Science and Technology, 2015)
The fluvio-deltaic deposit of the Thimi Formation constitutes the uppermost part of the sedimentary sequence in the Kathmandu Basin, and is consists of carbonaceous clay, diatomaceous clay, silty-clay, silt, fine to medium grained sand, and thin to medium lignite beds. A 25 m thick fresh surface exposure of this formation at Phaidhoka, Bhaktapur yielded significant number of vertebrate fossils. The vertebrate fossils recovered from a sand bed at 14 m from the bottom of the sequence consist of six teeth. The teeth were identified as Bovid teeth. Along with Bovid molars fragments of limb and pelvic bones were also found belonging to the same individual. Journal of Institute of Science and Technology, 2015, 20(2): 73-75